2023
DOI: 10.23876/j.krcp.22.211
|View full text |Cite
|
Sign up to set email alerts
|

Overview of aristolochic acid nephropathy: an update

Qingqing Zhou,
Lei Jiang,
Tao Su
et al.

Abstract: Aristolochic acid nephropathy (AAN) is a rapidly progressive renal interstitial fibrosis caused by medical or environmental exposure to aristolochic acid (AA). Since the outbreak of AAN in Belgium was reported nearly 30 years ago, the safety of herbal remedies has drawn considerable attention, and AAN has become a global public health problem. Breakthroughs have been made to better understand the disease, including the toxicity of AAs, the possible mechanisms of AAN, the disease patterns, and the pathological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 81 publications
0
2
0
Order By: Relevance
“…AAI belongs to the aristolochic acids (AAs) family, characterized by nitrophenanthrene carboxylic acids commonly present in plants of the Aristolochiaceae family, with prominent occurrences in the Aristochia and Asarum genera (Figure 1A). 1,2 Herbal remedies and products frequently incorporate AAs to address colds, headaches, aphthous stomatitis, inflammatory conditions, snakebites, and sexual dysfunctions. 1,3 However, it is crucial to note that exposure to AAs constitutes a notable risk for severe nephropathy and a spectrum of malignancies such as urological and hepatobiliary cancers.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…AAI belongs to the aristolochic acids (AAs) family, characterized by nitrophenanthrene carboxylic acids commonly present in plants of the Aristolochiaceae family, with prominent occurrences in the Aristochia and Asarum genera (Figure 1A). 1,2 Herbal remedies and products frequently incorporate AAs to address colds, headaches, aphthous stomatitis, inflammatory conditions, snakebites, and sexual dysfunctions. 1,3 However, it is crucial to note that exposure to AAs constitutes a notable risk for severe nephropathy and a spectrum of malignancies such as urological and hepatobiliary cancers.…”
mentioning
confidence: 99%
“…AAI belongs to the aristolochic acids (AAs) family, characterized by nitrophenanthrene carboxylic acids commonly present in plants of the Aristolochiaceae family, with prominent occurrences in the Aristochia and Asarum genera (Figure A). , Herbal remedies and products frequently incorporate AAs to address colds, headaches, aphthous stomatitis, inflammatory conditions, snakebites, and sexual dysfunctions. , However, it is crucial to note that exposure to AAs constitutes a notable risk for severe nephropathy and a spectrum of malignancies such as urological and hepatobiliary cancers. Research involving 67 Balkan patients with urinary tract tumors revealed that over two-thirds exhibited AA-DNA adducts in their renal cortex, with nearly half testing positive for the TP53 gene. , A study published in Science in 2017 pointed out that the widespread use of AA-containing traditional Chinese medicines is a major contributor to the incidence of liver cancer in Asia .…”
mentioning
confidence: 99%